2018
DOI: 10.1007/s13239-018-00385-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peak Wall Stress in an Ascending Thoracic Aortic Aneurysm Using FSI Simulations: Effects of Aortic Stiffness and Peripheral Resistance

Abstract: Purpose. It has been reported clinically that rupture or dissections in thoracic aortic aneurysms (TAA) often occur due to hypertension which may be modelled with sudden increase of peripheral resistance, inducing acute changes of blood volumes in the aorta. There is clinical evidence that more compliant aneurysms are less prone to rupture as they can sustain such changes of volume. The aim of the current paper is to verify this paradigm by evaluating computationally the role played by the variation of periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…open sci. 7: 191752 Few FSI studies have been performed on anatomically realistic aneurysms models to date [28][29][30]. Torii et al investigated FSI in two cerebral aneurysms showing that wall deformation affects the distribution of WSS.…”
Section: Introductionmentioning
confidence: 99%
“…open sci. 7: 191752 Few FSI studies have been performed on anatomically realistic aneurysms models to date [28][29][30]. Torii et al investigated FSI in two cerebral aneurysms showing that wall deformation affects the distribution of WSS.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they found the largest differences between rigid and deformable wall simulations occur during peak systole when wall deformation is greatest. Another study focusing on effects of hypertension and wall stiffness found that stiffer TAAs were correlated with the largest amount of altered wall stress distributions (Campobasso et al, 2018). Taken together, these computational studies demonstrate the importance of subject-specific modeling when simulating TAA initiation, progression, wall stresses, and rupture risk.…”
Section: Thoracic Aortic Aneurysmsmentioning
confidence: 73%
“…VVUQ of aneurysm CFD models has recently gained greater attention as the field has matured (Cebral et al, 2011a;Fiorella et al, 2011;Putman et al, 2011;Steinman, 2011). Campobasso et al (2018) modeled ascending TAAs, both verifying and validating their results with 4D flow MRI. However, since imaging methods for directly validating CFD model results in vivo are fraught with uncertainty themselves, direct validation remains challenging (Augst et al, 2003;Boussel et al, 2009).…”
Section: Validationmentioning
confidence: 79%
“…It is still important to remember that such spontaneous overstretch of the aortic wall is concomitant with a sudden rise of the blood pressure but it would never be directly related to WSS. Overpressure is likely to provoke a spontaneous aTAA rupture, [28] while WSS is expected to play a role in the longterm aTAA wall remodeling, possibly associated to the phenomenon of "outward convection" rather than rupture.…”
Section: About the Correlation Of Wss And Tawss With Aortic Wall Biommentioning
confidence: 99%